Assessing Bangladesh rice supply chain through SCOR modelling frame for planning effective integration of public and private actors. (2015) - Hossain, Moazzem; Jahan, Rawnak
This paper synthesises traditional Bangladesh rice industry with the help of extensive field survey, data collection and analysis. The characteristics of supply chain actors and interactions between/among the stakeholders are investigated; and based on the understandings, the rice supply chain is being mapped generally and also in popular supply chain operations reference (SCOR) frame. In the process, the relative strengths and weaknesses of various supply chain links and actors are identified; and gaps and missing links for effective integration of the supply chain actors (both public and private) are flagged. Based on the findings, an integrated supply chain model frame is suggested. Finally, the adequacy of the current government's policy frame and probable new policy initiatives, for guiding the effective integration of public and private actors, is critically discussed.